Introducing a new paradigm for accelerators and large experimental apparatus control systems - L. Catani; F. Zani; C. Bisegni; G. Di Pirro; L. Foggetta; G. Mazzitelli; A. Stecchi (Physical Review Special Topics. Accelerators and Beams, 2012)
The integration of web technologies and web services has been, in the recent years, one of the major trends in upgrading and developing distributed control systems for accelerators and large experimental apparatuses. Usually, web technologies have been introduced to complement the control systems with smart add-ons and user friendly services or, for instance, to safely allow access to the control system to users from remote sites. Despite this still narrow spectrum of employment, some software technologies developed for high-performance web services, although originally intended and optimized for these particular applications, deserve some features suggesting a deeper integration in a control system and, eventually, their use to develop some of the control system’s core components. In this paper, we present the conceptual design of a new control system for a particle accelerator and associated machine data acquisition system, based on a synergic combination of a nonrelational key/value database and network distributed object caching. The use of these technologies, to implement respectively continuous data archiving and data distribution between components, brought about the definition of a new control system concept offering a number of interesting features such as a high level of abstraction of services and components and their integration in a framework that can be seen as a comprehensive service provider that both graphical user interface applications and front-end controllers join for accessing and, to some extent, expanding its functionalities.